High-resolution ultrasonography of the first metatarsal phalangeal joint in gout: a controlled study. Issue 7 (21st December 2006) - Wright, Stephen A; Filippucci, Emilio; McVeigh, Claire; Grey, Arthur; McCarron, Maura; Grassi, Walter; Wright, Gary D; Taggart, Allister J
Abstract : Objective: To compare high-resolution ultrasound (HRUS) with conventional radiography in the detection of erosions in the first metatarsophalangeal joints (1st MTPJs) of patients with gout and to identify the characteristic sonographic features of gout. Methods: HRUS examination of the 1st MTPJs of both feet was performed by two independent sonographers. The presence of joint and soft-tissue pathology was recorded. x Ray examination of the feet was performed on the same day and reported by the same radiologist. Results: 39 male patients with gout and 22 age-matched control subjects (14 with an inflammatory arthropathy and 8 disease free) were studied. The agreement on erosion between HRUS and x ray was poor, κ = 0.229 (non-weighted), with McNemar's test being significant (p<0.001) indicating a large number of false negative x rays. 22 MTPJs in patients with gout had never been subjected to a clinical attack of acute gout. In these MTPJs, there were 10 erosions detected by HRUS and 3 erosions on x ray. HRUS features significantly more prevalent in the patients with gout were hard and soft tophus-like lesions (p<0.01) and the double contour sign (p<0.01). Conclusions: These data show that HRUS may assist in the management of gout in two ways: first, by aiding in the diagnosis by identifying the sonographic features that may be representative of the disease, and, second, by allowing the early detection of erosive joint damage and/or tophaceous deposits even in clinically silent joints.